Lipid rafts disruption by statins negatively impacts the interaction between SARS-CoV-2 S1 subunit and ACE2 in intestinal epithelial cells - El Khoury, Marianne; Naim, Hassan Y. (Frontiers in Microbiology, 2024)
The causative agent of the COVID-19 pandemic, SARS-CoV-2, is a virus that targets mainly the upper respiratory tract. However, it can affect other systems such as the gastrointestinal (GI) tract. Therapeutic strategies for this virus are still inconclusive and understanding its entry mechanism is important for finding effective treatments. Cholesterol is an important constituent in the structure of cellular membranes that plays a crucial role in a variety of cellular events. In addition, it is important for the infectivity and pathogenicity of several viruses. ACE2, the main receptor of SARS-CoV-2, is associated with lipid rafts which are microdomains composed of cholesterol and sphingolipids. In this study, we investigate the role of statins, lipid-lowering drugs, on the trafficking of ACE2 and the impact of cholesterol modulation on the interaction of this receptor with S1 in Caco-2 cells. The data show that fluvastatin and simvastatin reduce the expression of ACE2 to variable extents, impair its association with lipid rafts and sorting to the brush border membrane resulting in substantial reduction of its interaction with the S1 subunit of the spike protein. By virtue of the substantial effects of statins demonstrated in our study, these molecules, particularly fluvastatin, represent a promising therapeutic intervention that can be used off-label to treat SARS-CoV-2.